Diversity and Systematics Study of Tribe Alpinieae (Zingiberaceae) in Sarawak - Salasiah, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2021)
Family Zingiberaceae formed an important herbaceous layer in the tropical forests of Borneo. From the phylogenetic view, certain genera of the problematic tribe Alpinieae are non-monophyletic and in need of more taxonomic evidence to support the classification. This study demonstrates how the morphological, anatomical, palynological, and phytochemical evidences, correlated to the proposed phylogenetic data, taking representatives from the Bornean species. Furthermore, the rapid deforestation of the forests in Sarawak has also urged the assessment of the distribution and diversity of the species. Overall, 45 taxa from 11 genera were identified, including a newly described species and variety, Sundamomum corrugatum, and Plagiostachys strobilifera var. conica, respectively. Comprehensive morphologies of the fruit, anther crest, anther dehiscent, stigma, ostiole, labellum, lateral staminodes, and leaf sheaths were important in delimiting the species and genera in the tribe. The studied species were conveniently divided into two major groups based on the exine sculpturing of the spheroidal pollens, either psilate as in Etlingera and Hornstedtia, or echinate as in the remaining genera. Likewise, vegetative anatomical assessment unveiled informative characteristics in distinguishing the species. Phytochemical study of the rhizomes essential oils further revealed the major and specific components that characterised each studied cluster. Additionally, Lambir Hills National Park recorded the most diverse and stable area for Alpinieae species that could function as an important in-situ conservation area in Sarawak.